2023
DOI: 10.1371/journal.pone.0283046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with chronic school absenteeism among 207,107 in-school adolescents: Findings from cross-sectional studies in 71 low-middle and high-income countries

Abstract: Background Despite the negative impact of chronic school absenteeism on the psychological and physical health of adolescents, data on the burden of adolescent chronic school absenteeism (ACSA) and interventions and programs to address it are lacking. We estimated the global, regional and national level prevalence of ACSA and its correlation with violence and unintentional injury, psychosocial, protective, lifestyle, and food security-related factors among in-school adolescents across low and middle-income, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Social competence refers to effectiveness in social skills as well as the presence of adaptive interpersonal relationships (Persich and Robinson, 2022). Chronic school absenteeism has been linked to greater social isolation and peer victimization, less peer support and social engagement, and fewer friendships (Gottfried, 2014;Rahman et al, 2023). Children with SAPs also exhibit greater loneliness and negative affect than their school-attending peers (Jones and Suveg, 2015).…”
Section: Social-emotional Functioningmentioning
confidence: 99%
“…Social competence refers to effectiveness in social skills as well as the presence of adaptive interpersonal relationships (Persich and Robinson, 2022). Chronic school absenteeism has been linked to greater social isolation and peer victimization, less peer support and social engagement, and fewer friendships (Gottfried, 2014;Rahman et al, 2023). Children with SAPs also exhibit greater loneliness and negative affect than their school-attending peers (Jones and Suveg, 2015).…”
Section: Social-emotional Functioningmentioning
confidence: 99%
“…Previous research has shown that being socially integrated and experiencing school belonging has several positive implications [6][7][8]31,35,37,38]; therefore, motivating the students to stay at school is important. Moreover, in light of the effects of COVID-19 and students' increased level of school absenteeism and refusal worldwide [54], it might be more important than ever to work systematically with building an inclusive and good psychosocial environment where students are motivated to stay. As implicated from the results in this study, there might be a need for working systematically with higher intensity at all grade levels to build a good psychosocial environment, and not merely in the first grade of upper secondary school.…”
Section: Academic Adjustmentmentioning
confidence: 99%
“…School attendance problems have long been recognized as a critical developmental challenge and limiting factor for children and adolescents (Kearney, 2021). A wide array of academic deficiencies, internalizing behavior problems such as anxiety, depression, social isolation, as well as externalizing behavior problems such as elevated alcohol, tobacco, and drug use have been connected to this problematic (Kearney et al, 2023;Rahman et al, 2023). School attendance problems are the main focus of interest shown by researchers in the field of Education.…”
Section: Introductionmentioning
confidence: 99%